Numerical Homogenization of Protective Ceramic Composite Layers using the Hybrid Finite-Discrete Element Methods - Mohd Jaini, Zainorizuan; Feng, Yuan Tian; Mokhatar, Shahrul Niza; Abu Seman, Mazlan (International Journal of Integrated Engineering, 2013)
Innovative technologies have resulted in more effective ceramic composite as high rate loading-resistance and protective layer. The ceramic composite layer consists of ceramic frontal plate that bonded by softer-strong reinforced polymer network, consequently gains the heterogeneous condition. These materials serve specific purposes of defeating high rate loading and maintaining the structural integrity of the layer. Further due to the lack of a constituent material and tedious problem in heterogonous material modelling, a numerical homogenization is employed to analyse the isotropic material properties of ceramic composite layer in homogenous manner. The objective of this study is to derive a constitutive law of the ceramic composite using the multi-scale analysis. Two-dimensional symmetric macrostructure of the ceramic composite was numerically modelled using the hybrid finite-discrete element method to investigate the effective material properties and strength profile. The macrostructure was modelled as brittle material with nonlinear material properties. The finite element method is incorporated with a Rankine-Rotating Crack approach and discrete element to model the fracture onset. The prescribed uniaxial and biaxial loadings were imposed along the free boundaries to create different deformations. Due to crack initiation on the macrostructure, the averaged stresses were calculated to plot the stress-strain curves and the effective yield stress surface. From the multi-scale analysis, the rate-dependency of Mohr-Coulomb constitutive law was derived for the ceramic composite layer.